Exploring the Connection: How Does Fluid Restrictive Intermittent Fasting Affect Benign Anorectal Diseases? - Kudaş, İlyas; Başak, Fatih; Tosun, Hüsna; Çalışkan, Yahya Kemal; Zekey, Fethi Sada; Acar, Aylin; Canbak, Tolga (Journal of Coloproctology, 2025)
Introduction Intermittent fasting (IF) has gained popularity in recent years as a potential tool for promoting health and reducing disease risk. However, little research has been done on the impact of fluid restrictive IF on benign anorectal diseases. In this study, we aim to explore the effects of long periods of IF on conditions such as hemorrhoids and anal fissures, focusing on the potential role of other influencing factors.Materials and Methods This study utilized a cohort design to examine the changes in admissions for hemorrhoidal disease and anal fissure during Ramadan, a period of intermittent fasting with fluid restriction, compared to the remainder of the year. Patients admitted with these conditions between January 1, 2010, and December 31, 2019, were divided into two groups: the Ramadan group and the control (non-Ramadan) group. The primary endpoint of the study was to determine any significant differences in admissions between the two groups.Results The results showed that a total of 49,046 patients (0.68% of all admissions) were admitted with hemorrhoidal disease, and 33,480 patients (0.45%) with fissures were reviewed. Admissions for hemorrhoidal disease were significantly higher in the Ramadan group at 0.9%, compared to the control group (non-Ramadan) at 0.7% (p < 0.001). However, no increase was observed in the admittance rate for fissures between the two groups.Conclusion This study explores the potential connection between fluid restrictive IF and anorectal disease incidence, shedding light on this under-researched area. Findings suggest that extended periods of IF may increase the risk of hemorrhoidal disease, highlighting the need for clinicians and individuals adopting such regimes to consider related risk factors.
Keywords: fasting; hemorrhoids; anal fissure; intermittent fasting